Influence of the Irradiance on the Detection and Performance of PID-Affected PV-Modules - Buerhop-Lutz, Claudia; Pickel, Tobias; Wenz, F.; Zetzmann, Cornelia; Hauch, Jens; Camus, Christian; Brabec, Christoph (35th European Photovoltaic Solar Energy Conference and Exhibition, 2018)
Potential induced degradation (PID) is still a severe problem in many PV-installations and a huge financial risk for investors and plant-owners if not detected early. In previous investigations it was shown that thermography, conducted with handheld or drone mounted IR-cameras, is a fast and reliable tool to detect PID affected PV-modules on site and estimate their remaining electrical power during normal plant operation. In this work we show how to improve the sensitivity of IR- and various other imaging techniques by using the characteristic behavior of PID affected cells regarding the different excitation forces, i.e. solar irradiance for IR- and electric current for DLIT- and EL-measurements. Furthermore, we address the implications of this specific behavior by simulating the energy yield of several PID affected PV-strings based on real monitoring data for two inspected sites and suggest carrying out the measurements on site- and under failure- relevant conditions rather than standard test conditio
Keywords: Performance; Energy Yield; Thermography; Potential Induced Degradation; EL Imaging